The Physiological Differential Response Of Sugar Cane (Saccharum Officinaruml.) On Water Deficit Condition - Renfiyeni Renfiyeni; Rhenly Danis; Dila Febria; Ishak Manti (JERAMI : Indonesian Journal of Crop Science, 2019)
Abstract Sugarcane is the main sugar-producing plant in the world and also plays an important role as a raw material for bioethanol production. Productivity improvement of the plant is exposed to environmental stress ie: water shortage which is currently a serious problem associated with the global climate change phenomenon. Understanding of plant responses to environmental stress is one of the keys to be able to resolve the issue. In this regard, the fundamental studies related to the sugarcane plant responses to water stress is very important. This study consists of a combination of two factors, namely the type of clones consisting of PS.864, PSJT.941, and VMC.76-16, 851 as tolerant group clones, PS.862, PS.882 and PS.851as non tolerant clones group and lack of water stress treatment for 5 days. The data were analyzed further using DNMRT at 5% significance level. Observations showed that tolerant clones as well as non-tolerant clones PS.862 showed better resistance response than non tolerant groups. The indication was shown by the value of the Relative Water Content (RWC), Specific leaf area (SLA) and Water Deficit Value (WDV). Total protein profiling of sugarcane grown under water deficit and its counterpart differentially distinguished by suppression of protein expression of about 35 kDa in all clones. While in the water deficit condition expression of a protein with a size of 25 kDa is remarkable expressed.